2016
DOI: 10.5539/jedp.v6n1p131
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Attention and Its Relationship to Fluid Intelligence and Working Memory in Children

Abstract: Understanding individual differences in intelligence remains an interesting research question, even with more than a century of empirical research and large numbers of models and theories. We know that working memory (WM) is able to explain substantial amounts of variance in fluid intelligence in both children and adults, but we also know that it is not the only predictor of intelligence. There are many other information-processing mechanisms that have been studied. Results in adult samples seem to indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
4
0
3
Order By: Relevance
“…It is customary to distinguish the many factors and markers that influence mental development at an early age. Among them are motor development (Frick & Mohring, 2013), speech development (Tsao, Liu & Kuhl , 2004), working memory (Cowan & Alloway, 2009), sustained attention (Voelke & Roebers, 2016), spatial thinking (Lauer & Lourenco, 2016), cognitive control mechanisms (Engel de Abreu, Conway & Gathercole, 2010), and social intellect (Wellman et al, 2008. However, the role of these factors as predictors of DD at a particular age is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It is customary to distinguish the many factors and markers that influence mental development at an early age. Among them are motor development (Frick & Mohring, 2013), speech development (Tsao, Liu & Kuhl , 2004), working memory (Cowan & Alloway, 2009), sustained attention (Voelke & Roebers, 2016), spatial thinking (Lauer & Lourenco, 2016), cognitive control mechanisms (Engel de Abreu, Conway & Gathercole, 2010), and social intellect (Wellman et al, 2008. However, the role of these factors as predictors of DD at a particular age is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, increased alpha oscillation power at the occipital site is also connected to increased tonic alertness or vigilance 47 , 48 and internally directed attention 49 . This enhanced alertness may also trigger a temporary enhancement of cognitive functions 35 37 . Thus, music listening boosts-up cognitive abilities directly by increasing the local neural efficiency, and indirectly by enhancing sustained attention.…”
Section: Discussionmentioning
confidence: 99%
“…The important regions responsible for sustained attention is fronto-parietal system 33 . Some preliminary studies have indicated that music listening broadens the range of attention 34 and a notable contribution to intelligence’ variance is explained by attention control capacities 35 37 . Thus, this suggests a possible link among music, attention, and intelligence.…”
Section: Introductionmentioning
confidence: 99%
“…На сегодняшний день известно, что толщина коры больших полушарий созревает раньше, чем площадь поверхности коры: к возрасту 2 лет толщина коры достигает приблизительно 97% от взрослых значений, тогда как площадь поверхности коры достигает лишь 69% от взрослых значений (Haartsen et al, 2016). Функциональные сети покоя, измеряемые с помощью МРT, начинают появляться до рождения и продолжают развиваться в течение первых лет жизни, характеризуясь все более тонкой настройкой и повышением специализации (Vertes & Bullmore, 2014), при этом, топологическая эффективность нейронных сетей положительно коррелирует с IQ (Li et al, 2009) и производительностью внимания (Kitzbichler et al, 2011). Максимальное количество синаптических связей в медиальной префронтальной коре в нормальном онтогенезе отмечается в возрасте 3-4 лет, и остается таковым вплоть до подросткового возраста (Wierenga et al, 2014).…”
Section: исследования развития 3-летних детейunclassified
“…При этом, полученная модель полностью соответствует скринингу Denver(Dawson & Camp, 2014) по фактору моторного развития; речевое развитие и коммуникация представленные в западном скрининге в нашей модели соответствуют фактору общей осведомленности, предполагающему достаточное речевое развитие ребенка для расширения представлений о мире и сформированную коммуникацию на уровне, позволяющем аккумулировать вербальные знания; социальная адаптация в полученной нами модели не представлена, однако, выявлены факторы логического суждения и исполнительных функций, которые фактически, являются отражением структурно-функционального дозревания мозга и необходимой нейрофизиологической базой для адаптивного поведения.Заслуживает внимания, что при сравнении типично развивающихся детей и детей с ЗПР, трудности в обучении последних, отражают общие ограничения интеллектуального функционирования, связанные в первую очередь с проблемами внимания, исполнительных функций, грубой и мелкой моторики и с отсутствием компенсаторных стратегий(Cornoldi et al., 2005). Многие исследователи подчеркивают некоторую степень ограничения в развитии двигательных навыков у детей с когнитивной задержкой(Fernell & Ek, 2010;Vuijk et al, …”
unclassified